Pretibial mucinosis in an euthyroid patient - Laura de Mattos Milman; Aline Barcellos Grill; Giana Paula Müller; Damiê De Villa; Paulo Ricardo Martins Souza (Sociedade Brasileira de Dermatologia, 2016)
Abstract A case of exuberant pretibial mucinosis in a patient with normal thyroid function is reported. A review of literature on possible etiologies other than thyroid disease for the accumulation of mucin in the pretibial area is presented. In the patient described, it is possible that vascular insufficiency is involved. However, this is not the only factor responsible for the accumulation of mucin, since there are still unidentified causes and many patients with vascular diseases do not develop similar injuries.